Beyond Usability: Uncovering the Paradox of Website Quality and User Satisfaction in Indonesian Higher Education - Ilham Chandra Pangestu; Murhadi; Ike Yunia Pasa (Indonesian Technology and Education Journal, 2026)
This study aims to examine the effects of usability quality, information quality, and service interaction quality on user satisfaction with the official website of Muhammadiyah University of Purworejo using the WebQual 4.0 framework, supported by Importance-Performance Analysis (IPA). A descriptive quantitative approach was employed, with data collected through an online questionnaire distributed to 130 active students selected using non-probability convenience sampling; 30 responses were used for validity and reliability testing, while 100 responses were analyzed in the main study. The data were processed using IBM SPSS Statistics 26 through Pearson correlation, Cronbach’s Alpha, multiple linear regression, partial t-tests, coefficient of determination, and IPA. The findings reveal that usability quality has a negative and significant effect on user satisfaction (β = −0.168; p = 0.037), whereas information quality (β = 0.284; p = 0.001) and service interaction quality (β = 0.533; p = 0.000) have positive and significant effects, with service interaction quality emerging as the strongest predictor. The model explains 67.6% of the variance in user satisfaction. The originality of this study lies in its explanation of the negative usability effect through expectation-disconfirmation theory and the Technology Acceptance Model, as well as its integration of WebQual 4.0 regression with IPA to generate prioritized improvement strategies. The findings imply that UMPWR website managers should urgently improve interface usability, maintain strong service interaction quality, and sustain accurate and timely information provision to enhance user satisfaction.